Intuit Quickbooks Accounting 2009 for Mac the 800-pound gorilla's new clothes. - Gripman, Stuart
Inuit Quickbooks Accounting 2009 is a bookkeeping software for Mac.
Keywords: QuickBooks; Accounting -- Computer programs; Bookkeeping -- Computer programs